1984
DOI: 10.1002/ange.19840960106
|View full text |Cite
|
Sign up to set email alerts
|

Die Cycloaddition von Allyl-Kationen an 1,3-Diene: Eine allgemeine Methode zur Synthese siebengliedriger Carbocyclen

Abstract: Allyl-Kationen reagieren rnit 1J-Dienen zu sieben-, fiinf-und sechsgliedrigen Ringen, aber auch zu Produkten der elektrophilen Substitution und zu linearen 1 : 1-Addukten. In diesem Beitrag werden Fortschritte auf prlparativem und mechanistischem Gebiet zusammenge-faBt, wobei die Synthese siebengliedriger Carbocyclen im Mittelpunkt steht. Es wird erstmals eine umfassende mechanistische Beschreibung vorgestellt : Drei Reaktionsklassen set-Zen den Produkttyp und die resultierende Stereochemie in Beziehung zur Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(16 citation statements)
references
References 70 publications
0
14
0
2
Order By: Relevance
“…[1,2] In recent years, investigations into this type of cycloaddition, including a number of elegant applications in total synthesis, [3] have demonstrated its potential for development as a synthetic method that could approach the (4+2) cycloaddition (Diels-Alder) reactions in terms of selectivity and efficiency. Of particular interest are allylic cations bearing a cation-stabilizing substituent (Z group) at the 2-position [Eq.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] In recent years, investigations into this type of cycloaddition, including a number of elegant applications in total synthesis, [3] have demonstrated its potential for development as a synthetic method that could approach the (4+2) cycloaddition (Diels-Alder) reactions in terms of selectivity and efficiency. Of particular interest are allylic cations bearing a cation-stabilizing substituent (Z group) at the 2-position [Eq.…”
mentioning
confidence: 99%
“…Of particular interest are allylic cations bearing a cation-stabilizing substituent (Z group) at the 2-position [Eq. (1)] [4] and stabilized allylic cations such as vinyloxocarbenium ions [Eq. (2)] [5] or, typically, cationic reaction partners incorporating both of these features [Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During their campaign towards the synthesis of englerin A (1), Lin and co-workers took advantage of an organocatalytic [4+3] cycloaddition reaction developed previously by Harmata et al [51] In doing so, the group reported the first application of this underutilized reaction in the context of a target-oriented synthesis (Scheme 21). [52] Scheme 17.…”
Section: Lins Synthetic Approach Toward the Guaiane Core Of The Englementioning
confidence: 99%
“…[24] Die Cycloaddition von Allyl-Kationen mit Dienen hat sich in der Folgezeit zu einer allgemeinen Synthesemethode entwickelt. [25] Wichtige weitere [4+3]-Cyclisierungen wurden dann in den achtziger Jahren von Trost et al publiziert, denen aus 2-[(Trimethylsilyl)methyl]allylacetat (4) in Gegenwart von Palladium(0)-Katalysatoren die Bildung von Trimethylenmethan-Intermediaten gelang, die mit elektronenarmen Dienen wie 5 neben Vinyl-substituierten Methylencyclopentanen 6 auch Methylencycloheptene 7 lieferten (Schema 1). [26,27] Die erste Synthese eines Cycloheptanderivates durch [3+2+2]-Cyclisierung gelang Stryker und Schwiebert 1995, indem sie kationische Iridiumkomplexe, die aus dem Triflat 8 generiert worden waren, in situ mit terminalen oder internen Alkinen zu Cycloheptadienyl-Komplexen umsetzten.…”
unclassified